1998
DOI: 10.1172/jci119889
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the apoptosis-inducing activity of lupus anticoagulant in an annexin V-binding antibody subset.

Abstract: Lupus anticoagulant (LAC) is associated with arterial and venous thrombosis, thrombocytopenia, and recurrent fetal loss. We have reported previously that plasma with LAC activity induces apoptosis in endothelial cells and binds annexin V (Nakamura, N., Y. Shidara, N. Kawaguchi, C. Azuma, N. Mitsuda, S. Onishi, K. Yamaji, and Y. Wada. 1994. Biochem. Biophys. Res. Commun. 205:1488-1493). In this study, we separated two IgG antibody fractions, one with and one without affinity for annexin V, from 10 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 72 publications
0
29
2
1
Order By: Relevance
“…While this model is not designed to mimic the precise sequence of pathogenetic events linked to specific thromboinflammatory diseases, it nonetheless provides important insights into the molecular processes by which dying endothelial cells promote leukocyte trafficking in vivo. The disruption of membrane phospholipid asymmetry in endothelial cells leading to PS exposure is a characteristic feature of dying cells regardless of the cause 44,45 , as in the antiphospholipid syndrome 46 , in response to immunomodulatory and chemotherapeutic regimens containing agents such as thalidomide 47 and arsenic 48 , and after ischaemia reperfusion [49][50][51] . Therefore, our observations related to PS-positive endothelial cells after needle injury may have relevance to disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…While this model is not designed to mimic the precise sequence of pathogenetic events linked to specific thromboinflammatory diseases, it nonetheless provides important insights into the molecular processes by which dying endothelial cells promote leukocyte trafficking in vivo. The disruption of membrane phospholipid asymmetry in endothelial cells leading to PS exposure is a characteristic feature of dying cells regardless of the cause 44,45 , as in the antiphospholipid syndrome 46 , in response to immunomodulatory and chemotherapeutic regimens containing agents such as thalidomide 47 and arsenic 48 , and after ischaemia reperfusion [49][50][51] . Therefore, our observations related to PS-positive endothelial cells after needle injury may have relevance to disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…2A). ANX proteins are known to be involved in apoptosis in mammals and nematodes (Nakamura et al, 1998;Arur et al, 2003). As 20E triggers PCD of the silk glands, the reciprocal expression of ANX IX and the change in hemolymph ecdysteroid titer suggest a relationship between ANX IX and 20E-induced PCD.…”
Section: Discussionmentioning
confidence: 99%
“…LAC inhibits coagulation in vitro, but is paradoxically associated with thrombosis in affected patients. Recently it was shown that LAC induces apoptosis in endothelial cells and binds annexin V, a protein that has been suggested to play a role in preventing blood coagulation (9).…”
Section: Discussionmentioning
confidence: 99%